Policy-making as designing : the added value of design thinking for public administration and public policy - Buuren, Arwin van; Lewis, Jenny M.; Peters, B. Guy (New perspectives in policy & politics., 2023)
Design approaches to policymaking have gained increasing popularity among policymakers in recent years. First published as a special issue of Policy & Politics, this book presents original critical reflections on the value of design approaches and how they relate to the classical idea of public administration as a design science. Contributors consider the potential, challenges and applications of design approaches and distinguish between three methods currently characterising the discipline: design as optimisation, design as exploration and design as co-creation. Developing the dialogue around public administration as a design science, this collection explores how a more 'designerly' way of thinking can improve public administration and public policy.--